A survey of expectations of pet owners from veterinarians - Ozen, A; Onat, N; Ozturk, R; Yerlikaya, H; Seker, I (Indian Veterinary Journal, 2004)
In this study, a questionnaire completed by 228 clients of seven small animal clinics asked what clients expected and what they received in their interaction with the veterinarians. The results of this study supported the view that client expectation is not solely limited to pet's health in veterinary medicine. It could be said that client satisfaction is related to counselling service as much as veterinary medical services.